2020
DOI: 10.3766/jaaa.18101
|View full text |Cite
|
Sign up to set email alerts
|

Vestibular Screening in Pediatric Patients with Otitis Media

Abstract: Otitis media with effusion (OME) is a common cause of vestibular disturbances in children. However, young children often lack the language to express their symptoms, and it is uncommon to screen children for vestibular impairments.The purpose of this study was to develop a screening protocol for children presenting with OME to determine if diagnostic vestibular testing is necessary.Children with normal hearing (NH), sensorineural hearing loss (SNHL), and conductive hearing loss (CHL) due to OME participated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…After analyzing all the studies included in the integrative review, eight experimental studies were found, six of which were randomized clinical trials (level of evidence 2) 12 , 13 , 14 , 15 , 16 , 17 and two non-randomized ones (level of evidence 3) 18 , 19 ; eighteen observational studies (level of evidence 4) 5 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ; and six case studies (level of evidence 5), 36 , 37 , 38 , 39 , 40 , 41 according to the classification used. 11 …”
Section: Resultsmentioning
confidence: 99%
“…After analyzing all the studies included in the integrative review, eight experimental studies were found, six of which were randomized clinical trials (level of evidence 2) 12 , 13 , 14 , 15 , 16 , 17 and two non-randomized ones (level of evidence 3) 18 , 19 ; eighteen observational studies (level of evidence 4) 5 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ; and six case studies (level of evidence 5), 36 , 37 , 38 , 39 , 40 , 41 according to the classification used. 11 …”
Section: Resultsmentioning
confidence: 99%
“…Acute otitis media is a fairly common pathological process of the middle ear among preschool children [13,14]. Previous studies have revealed symptoms of latent vestibular pathology in children with secretory otitis media [14,18,19,21]. However, only a small number of these studies focus on a narrow age range -preschool age [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…The study of coordination, balance, oculomotor function and nystagmus in children 4-8 years with otitis media with effusion revealed a significant increase in oculomotor abnormalities compared with the control [18]. A study of 4-15-year-old children with otitis media with effusion and dizziness by video pulse vestibulo-ocular test (vHIT) did not reveal significant changes in the mean values of vHIT growth or their asymmetry, however, revealed an increased frequency of latent saccades (57 %), which was considered by the authors as a sign of mild vestibular disorder [19].…”
Section: Introductionmentioning
confidence: 90%
“…The WHO has stipulated that approximately 50% of individuals with acute otitis media (AOM) will develop chronic suppurative otitis media (CSOM) (Mahy et al, 2019 ). Further complications of untreated middle ear pathologies include permanent hearing impairment (Hutz et al, 2018 ), meningitis (Avnstorp et al, 2016 ), facial paralysis (Lawler, 2018 ), and vestibular disturbances (Rehagen et al, 2019 ). The impacts of these conditions in children can have far-reaching consequences.…”
Section: Introductionmentioning
confidence: 99%